Comparison between a fixed-dose contrast protocol and a weight-based contrast dosing protocol in abdominal CT. Issue 12 (December 2016) - George, A.J.; Manghat, N.E.; Hamilton, M.C.K.
Abstract : Aim: To compare a fixed-dose intravenous iodinated contrast medium protocol with weight-based dosing protocols for abdominal computed tomography (CT). Materials and methods: Fifty patients were scanned using a fixed-dose protocol, 50 patients were scanned using a full-dose weight-based contrast dosing protocol, and 13 patients were scanned using a reduced dose weight-based protocol. Radiodensity was measured at the portal vein, aorta, spleen, and liver. These values were plotted against contrast medium dose per unit weight. Images from all patients were anonymised and presented to two independent consultants who subjectively assessed contrast enhancement using a five-point Likert scale. Results: Using a fixed-dose protocol, there was a statistically significant negative correlation and trend between patient weight and radiodensity at the portal vein, aorta, spleen, and liver. Using a full-dose weight-based contrast dosing protocol, there was no longer a statistically significant correlation or trend implying a more consistent degree of enhancement over a spectrum of patient weights. In addition, when the full-dose weight-based contrast dosing protocol was used, there was a statistically significant increase in the number of scans subjectively assessed as having ideal enhancement and a statistically significant decrease in the number of scans felt to have excessive enhancement when compared to a fixed-dose protocol. The weight-based dosing protocol used less contrast medium than the fixed-dose protocol and there was no evidence of contrast-induced acute kidney injury (CIAKI) in any of the patients that received a greater dose than that which they would have received using a fixed-dose protocol. The reduced-dose weight-based protocol showed less objective enhancement of the portal vein, abdominal aorta, spleen, and liver compared to the full-dose protocol and a reduction in the number of scans perceived as showing ideal enhancement. There was, however, no increase in the number of scans with poor or non-diagnostic enhancement. Conclusion: Weight-based contrast medium dosing has been shown to objectively provide more consistent vessel and solid-organ enhancement and subjectively improve image quality across a spectrum of weights. Depending on mean patient mass, it has also been shown to reduce overall contrast medium dose, and there is no evidence of CIAKI in patients that receive larger doses. This study also postulates that a standardised approach to contrast medium dose reduction in patients with renal impairment may be a viable strategy. Highlights: A fixed contrast dosing protocol, results in a negative correlation and trend between patient weight and Hounsfield units. There is no correlation or trend between patient weight and Hounsfield units using a weight-based contrast dosing protocol. Weight-based contrast dosing provides more consistent image quality. More consistent image quality may improve lesion detection in abdominal CT scanning. Depending on mean patient mass a weight-based contrast dosing protocol can reduce overall contrast dose. There is no evidence of CI-AKI in patients that receive larger doses in the weight-based contrast dosing cohort A standardised approach to reducing contrast doses by weight in patients with renal impairment may be a viable strategy.